Pemecahan Masalah Keluarga melalui Pengungkapan Diri di Media Sosial X - Amaria, Meilani; Nurmasitah, Sita (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2026)
This study aims to analyze various types of family issues revealed on social media platform X through the community account @tanyakanrl, and to discuss the role of this account as a means of self-expression. The study focuses on the dynamics of family problems from September to November 2025, using a descriptive quantitative approach and purposive sampling method on 168 posts that met the criteria. The data were analyzed by categorizing each post based on indicators of family issues, such as communication among family members, finances, parent-child conflicts, jealousy, infidelity, and domestic violence. The study shows that individuals actively and continuously express themselves. Overall, this study illustrates how various family issues emerge and develop in digital self-disclosure. For researchers, the results of this study can serve as a foundation for further studies on how individuals express themselves on social media and the topics they frequently discuss. Meanwhile, for individuals engaging in self-disclosure, the presence of such accounts provides a safe space to express emotions, receive support, and gain a sense of security and comfort when engaging in disclosure communication without fear of social stigma. However, this study has limitations, including a relatively short research period, a time-consuming process of reviewing sample posts, and difficulties in verifying user identities due to anonymity.